The distribution and abundance of wetland ichthyofauna, and exploitation of the fisheries in the Godineau Swamp, Trinidad – Case study - Ramsundar, Himawatee (2005)
The Godineau (South Oropuche) Swamp (3171 ha) on the southwestern coast of Trinidad (10º13- 15’N, 61º30-32’W) is heavily impacted by anthropogenic activities including fishing, oil exploration, drainage manipulation and wetland clearance. To reduce the negative effects of these activities and to manage the swamp more sustainably, more quantitative information is needed on the ecology of the wetland and the activities that occur within it. This study focuses on the distribution of the fish resources and exploited fisheries as a basis for more informed management directives. Sampling was conducted during 2002, in April-May (for dry season) and July-September (for wet season sampling). Ichthyofauna was sampled both day and night using trammel nets and a push seine. Fishing activities were assessed using a questionnaire and informal discussions with fishers. The wetland supports over 29 species of fish distributed over the freshwater, estuarine and saline zones (n=1454). Species distribution is seasonal, with evidence of the wetland being used as a spawning ground. Species richness and species diversity (Shannon-Weiner Index) for the wetland ranged over 2-11 and 0.162-0.967, respectively, in the dry season and 2-7 and 0.036-0.903, respectively, in the wet season. Communities inhabiting the saline and estuarine zones of the wetland were dominated by a single species, Hexanematichthys bonillai. Percent Similarity Indices were 41.8% for freshwater, 72.7% for estuarine and 79.8% for estuarine-saline communities. The commercial species accounted for 18% of total catch sampled and consisted of Centropomus undecimalis, Megalops atlanticus, Hoplosternum littorale, Hoplias malabaricus, Ophioscion punctatissimus and Macrodon ancyclodon. Full-time and part-time fishers, including recreational fishers, accounted for 14.3% and 85.7%, respectively of all fishers surveyed (n=56). A conservative estimate of the revenue earned directly at point of sale for fish and shellfish, is approximately US$43 000 per annum. Fishing is important in the area. Management directives taking into account the ecology of the target organisms are needed to allow these fishing practices to be continued in a sustainable manner.